2012
DOI: 10.1007/s11434-012-5537-9
|View full text |Cite
|
Sign up to set email alerts
|

Multi-dimensional overall regulatory modes and threshold values for water cycle of the Haihe River Basin

Abstract: In this study, a multi-dimensional critical regulatory criteria and decision-making mechanism based on the scientific cognition of multi-dimensional attributes and characteristics of the water cycle was proposed. This system was functioned by deeply discriminating the nature-society binary characteristics of the five-dimensional characteristics of the water cycle system of the Haihe River Basin (water resources, economy, society, ecology, and environment) under the influence of high-intensity human activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Integrated accounting refers to the comprehensive calculation of water resource value through a certain model. Many existing studies have concluded that water resource value is only related to the unit price and quantity [74], ignoring the impact of water quality. In fact, water resource value is the unification of quality and quantity [35,47].…”
Section: Price Calculation Model Of Water Resourcementioning
confidence: 99%
“…Integrated accounting refers to the comprehensive calculation of water resource value through a certain model. Many existing studies have concluded that water resource value is only related to the unit price and quantity [74], ignoring the impact of water quality. In fact, water resource value is the unification of quality and quantity [35,47].…”
Section: Price Calculation Model Of Water Resourcementioning
confidence: 99%
“…One of the largest economic benefits is to make crops produce more, which involves maximizing the use of water resources to achieve the efficient utilization of water resources [19] .…”
Section: Modelingmentioning
confidence: 99%
“…Social benefits arise from making the output of grain meet the demands of human society, achieving fair social distribution, meeting the social demands of people's daily consumption and increasing farmers' income to maintain social stability and raise the quality of life of individuals [19] .…”
Section: Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, people have underestimated the calculated value of a portion of water resources. For example, the reduction in the value of resources caused by resource consumption in socio-economic activities has not been reflected in national economic accounting; thus, the external costs of socio-economic activities are underestimated, and this fails to completely reflect the comprehensive achievements of human society in its development [4]. In this context, the concept of "the sustainable development of water resources" was proposed.…”
Section: Introductionmentioning
confidence: 99%